EFFECT OF ETHANOLIC EXTRACTS OF CYAMOPSIS TETRAGONOLOBUS AND CYPERUS ROTUNDUS ON BIOCHEMICAL PARAMETERS OF DIABETIC CATARACT INDUCED WISTAR ALBINO RATS - SEEMA SURENDRAN; VIJAYALAKSHMI KRISHNAMOORTHY (International Journal of Pharma and Bio Sciences, 2014)
The present study evaluated the effect of ethanolic extracts of Cyamopsis tetragonolobus rhizomes and Cyperus rotundus pods on the biochemical parameters of diabetic cataract induced Wistar albino rats. Healthy rats were grouped into 4: Group I – Normal, Group II – Diabetic cataract induced animals (STZ-induced diabetic rats which developed cataract), Group III – Cyamopsis tetragonolobus extract co-treated animals and Group IV – Cyperus rotundus extract co-treated animals (Treatment for 19 weeks after STZ induction). Body weight and organ weight of cataract animals decreased while plant treatment prevented this loss. Increase in values of glucose, glycated haemoglobin, insulin, creatinine, urea and uric acid levels were observed in diabetic cataract induced rats, while plant co-treated groups restored these levels. The changes in lipid and protein profile in Group II rats were prevented by the plant treatment. SGOT, SGPT, ALP and LDH increased in Group II but plant treatment retained enzymatic activities. The results signify the plant’s protective nature.